PROFESIONALISME GURU PAI SMP DI KABUPATEN BANGKA SELATAN DALAM MENGIMPLEMENTASIKAN KURIKULUM - Robinson, Robinson (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2016)
Teachers as one compenen in learning activities (KBM), have that determine the success of teaching-learning process. the main role of the teacher are to design, manage, execute, and toevaluate learning. Therefore, how a teacher can be able to do their job properly, while is not professional in his duties and functions as a teacher. In this research, there are 15 junior high school teachers of Islamic Education (PAI) in South Bangka regency as a sample. This small number of sample has been taken because the small member of Islamic Education teachers in South Bangka regency. The data retrieved through questionnaires and documentation. After collecting data, it is analyzed by using qualitative to determine the level (category) Islamic Education teacher professionalism, Implementation of Curriculum through the Meanformula (average value), Standard Deviation and TSR (High, Medium and Low). A quantitative analysis is used to determine Islamic Education Teachers professionalism in implementing the curriculum through Kai Kwadrat formula, Correlation of Contingency and Phi. The result of this research is Islamic Educationteachers’ professionalism in Junior High School of South Bangka Regency have a significant influence on the Implementation of the Curriculum.